A transforming KIF5B and RET gene fusion in lung adenocarcinoma revealed from whole-genome and transcriptome sequencing - Ju, Young Seok; Lee, Won-Chul; Shin, Jong-Yeon; Lee, Seungbok; Bleazard, Thomas; Won, Jae-Kyung; Kim, Young Tae; Kim, Jong-Il; Kang, Jin-Hyoung; Seo, Jeong-Sun (Genome Research, 2012)
The identification of the molecular events that drive cancer transformation is essential to the development of targeted agents that improve the clinical outcome of lung cancer. Many studies have reported genomic driver mutations in non-small-cell lung cancers (NSCLCs) over the past decade; however, the molecular pathogenesis of >40% of NSCLCs is still unknown. To identify new molecular targets in NSCLCs, we performed the combined analysis of massively parallel whole-genome and transcriptome sequencing for cancer and paired normal tissue of a 33-yr-old lung adenocarcinoma patient, who is a never-smoker and has no familial cancer history. The cancer showed no known driver mutation in EGFR or KRAS and no EML4-ALK fusion. Here we report a novel fusion gene between KIF5B and the RET proto-oncogene caused by a pericentric inversion of 10p11.22–q11.21. This fusion gene overexpresses chimeric RET receptor tyrosine kinase, which could spontaneously induce cellular transformation. We identified the KIF5B-RET fusion in two more cases out of 20 primary lung adenocarcinomas in the replication study. Our data demonstrate that a subset of NSCLCs could be caused by a fusion of KIF5B and RET, and suggest the chimeric oncogene as a promising molecular target for the personalized diagnosis and treatment of lung cancer.
10.1101/gr.133645.111